Suprasellar arachnoid cyst presenting with amenorrhea and galactorrhea - (:unkn) unknown (My University, 2001)
Büyük bir suprasellar kisti olan 32 yaşındaki bir kadın bildirilmektedir. Hasta hiperprolaktinemiye bağlı olduğu saptanan amenore ve galaktore şikayeti ile kabul edilmişti. Bunlar, suprasellar araknoid kistlerde görülen değişik endokrinolojik bulgular arasında oldukça nadir olan semptomlardır. Olgunun MRI bulguları ve olguya cerrahi girişim yolları tartışılmıştır.

The authors report a case of large Suprasellar arachnoid cyst in a 32-year-old woman. The patient presented with amenorrhea and galactorrhea, which were both caused by hyperprolactinemia. These are rare symptoms among the various endocrinologic features that can accompany Suprasellar arachnoid cysts. The magnetic resonance imaging findings and surgical options are discussed.
Amenore ve galaktore ile seyreden suprasellar araknoid kist
Keywords: Cerrahi